The Extractive Industries Sector : Essentials for Economists, Public Finance Professionals, and Policy Makers - Halland, Havard; Lokanc, Martin; Nair, Arvind; Kannan, Sridar Padmanabhan (Washington, DC: World Bank, 2015)
The extractive industries (EI) sector occupies an outsize space in the economies of many developing countries. Economists, public finance professionals, and policy makers working in such countries are frequently confronted with issues that require an in-depth understanding of the sector. The objective of this volume is to provide a concise overview of EI-related topics these professionals are likely to encounter. The volume provides an overview of issues central to EI economics; discusses key components of the sector’s governance, policy, and institutional frameworks; and identifies the public sector’s EI-related financing obligations. Its discussion of EI economics covers the valuation of subsoil assets, the economic interpretation of ore, and the structure of energy and mineral markets. The volume maps the responsibilities of relevant government entities and outlines the characteristics of the EI sector’s legal and regulatory frameworks. Specific key functions of the sector are briefly discussed, as are the financial structures that underpin environmental and social safeguards; investment of public revenues generated from oil, gas, or minerals; as well as extractive-based economic diversification. The authors hope that decision makers in ministries of finance, international organizations, and other relevant entities will find the study useful to their understanding and analysis of the EI sector.